2009
DOI: 10.1063/1.3186039
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and piezoelectric properties of K0.5Na0.5NbO3–AgSbO3 lead-free ceramics

Abstract: Lead-free piezoelectric ceramics ͑1−x͒K 0.5 Na 0.5 NbO 3 -xAgSbO 3 + 0.75 mol % MnO 2 were prepared by a conventional solid-state sintering technique, and the piezoelectric and dielectric properties of the ceramics were studied. The results of x-ray diffraction suggest that AgSbO 3 diffuses into the K 0.5 Na 0.5 NbO 3 lattices to form a new solid solution with a single-phase orthorhombic perovskite structure. After the addition of AgSbO 3 , the paraelectric cubic-ferroelectric tetragonal phase transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…The pure LKNNT ceramics possess a typical bimodal distribution of grain size, where coarse grains are larger than 4 μm, but most fine grains are smaller than 1 μm in diameter, being similar to those of KNN‐based ceramics with different composition . After the addition of AgSbO 3 , the average grain size of LKNNT ceramics decreases and the microstructure becomes more uniform, being similar to the previous studies . It has been reported that the addition of Sb into KNN piezoceramics can greatly decrease its grain size, which indicates that the Sb 5+ in AS may play the same role in reducing the grain size of LKNNT ceramics.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The pure LKNNT ceramics possess a typical bimodal distribution of grain size, where coarse grains are larger than 4 μm, but most fine grains are smaller than 1 μm in diameter, being similar to those of KNN‐based ceramics with different composition . After the addition of AgSbO 3 , the average grain size of LKNNT ceramics decreases and the microstructure becomes more uniform, being similar to the previous studies . It has been reported that the addition of Sb into KNN piezoceramics can greatly decrease its grain size, which indicates that the Sb 5+ in AS may play the same role in reducing the grain size of LKNNT ceramics.…”
Section: Resultssupporting
confidence: 81%
“…A gentle decrease of T T‐O favors the precise control of T T‐O since its moderate dependence on doping content makes the preparation of the ceramics easier. Recent work found that the addition of AgSbO 3 (abbreviated as AS) into KNN or Li‐doped KNN could decrease the T T‐O of the ceramics more gently and lead to a more uniform and fine microstructure . What is more, it has been reported that the addition of Ag or Sb can lead to the changes of phase structure and enhance the piezoelectric properties of KNN‐based piezoceramics .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the hot‐pressed ceramics, the two diffraction peaks (202) and (020) of the KNNLB‐0.10/ y /0 ceramics have merged together (Fig. ), suggesting that they may transform into another phase with very similar lattice constants, e.g., pesudocubic . As the merged peaks of the KNNLB‐0.10/4/0 and KNNLB‐0.10/6/0 ceramics are sharper than the others, their crystal structure should be more cubic‐like.…”
Section: Resultsmentioning
confidence: 94%
“…Hence, it is specially urgent to search for lead‐free or low lead content materials that have excellent piezoelectric properties. As far as lead‐free piezoelectric materials are concerned, considerable attention has recently been given to (K 0.5 Na 0.5 )NbO 3 (KNN)‐based ceramics on account of their excellent piezoelectric properties, high Curie temperature 6 , and environmental friendliness 7–14 . A variety of additions have been made to KNN for forming new KNN‐based ceramics with improved densification and piezoelectric properties, such as KNN–LiSbO 3 , 15 KNN–LiNbO 3 10 .…”
Section: Introductionmentioning
confidence: 99%